Argument on biometrics identity‐based encryption schemes. Issue 11 (12th February 2013) - Tan, Syh‐Yuan; Jin, Zhe; Teoh, Andrew Beng Jin
ABSTRACT: Recently, a few biometric identity‐based encryption (BIO‐IBE) schemes have been proposed. BIO‐IBE leverages both fuzzy extractor and Lagrange polynomial to extract biometric feature as a user public key and as a preventive measure of collusion attack, respectively. In this paper, we reveal that BIO‐IBE is not realistic whereby a query of fresh biometrics is needed for each encryption process. Moreover, the use of both fuzzy extractor and Lagrange polynomial in BIO‐IBE simultaneously is a redundancy; it confers no advantage, but simply computational overhead. Therefore, we amend the progression of the BIO‐IBE scheme by eliminating either Lagrange polynomial or fuzzy extractor to alleviate computational complexity. Subsequently, we demonstrate that the amendment does not compromise the security of the BIO‐IBE scheme. Such amendments can be applied to other BIO‐IBE schemes as well. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We revealed that biometric identity‐based encryption (BIO‐IBE) is not realistic whereby a query of fresh biometric is needed for each encryption process. Moreover, the use of both fuzzy extractor and Lagrange polynomial in BIO‐IBE simultaneously is a redundancy. We amend the progression of the BIO‐IBE scheme by eliminating either Lagrange polynomial or fuzzy extractor to alleviate computational complexity without compromising the security of the BIO‐IBE scheme.